EFL Teachers’ Perceptions of Continuing Professional Development: A Case of Iranian High School Teachers (2015)
English, particularly regarding a foreign language teachers’ professional development, has been studied in depth. However, it is not known how Iranian English as a foreign language teachers perceive continuing professional development. This study explored the perceptions of Iranian English as a foreign language teachers of continuing professional development and identified their main professional development activities. For the study, a phenomenological research design was applied. Twenty English teachers were interviewed. The data were content analyzed in line with the Randor model. The results showed that the participants perceived continuing professional development to entail skills development, continuous learning, keeping up to date, learning for interest, and professional revitalization. Additionally, they developed professionally through work, formal education, and attending and presenting at continuing professional development events.El desarrollo profesional de los docentes de inglés como lengua extranjera se ha estudiado ampliamente. Sin embargo, se desconoce cómo los profesores iraníes de inglés como lengua extranjera perciben el desarrollo profesional continuado. En este estudio se exploran dichas percepciones y se identifican las principales actividades que estos docentes llevan a cabo para desarrollarse profesionalmente. Con este fin, se diseñó una investigación fenomenológica aplicada a 20 profesores entrevistados. Los datos se analizaron de acuerdo con el modelo propuesto por Radnor. Los resultados mostraron que los docentes perciben el desarrollo profesional continuado como: mejora de habilidades, aprendizaje continuo, actualización, aprendizaje motivado por el interés y revitalización de la labor docente. Asimismo, los docentes crecen profesionalmente por medio del trabajo, la educación formal y la asistencia y presentación en eventos de desarrollo profesional continuado.